Axinellamine E, One New Pyrrololactam Alkaloid from the South China Sea Sponge Axinella sp. Issue 7 (8th June 2022) - Xu, Li; Wang, Panpan; Yuan, Shijie; Yu, Liangzhou; Zhao, Jianping; Li, Guoqiang; Zhang, Gang; Luo, Lianzhong
Abstract: Chemical investigation of the EtOH extract of the sponge Axinella sp. collected from the South China Sea resulted in the identification of one new pyrrololactam alkaloid, axinellamine E (2 ), along with four known analogs (1, 3 –5 ). Compound 1 was initially separated as enantiomers and was further separated to be optically pure compounds (1 a and 1 b ) by a chiral column. The planar structure of compound 2 was determined mainly by 1D‐, 2D‐NMR, and HR‐ESI‐MS data analyses. Absolute configurations of 1 a and 1 b was defined by calculated ECD spectra method. All of the compounds were evaluated for their anti‐inflammatory activities against nitric oxide production in lipopolysaccharide‐induced RAW 264.7 cells among which compound 1 showed weak activity at 40 μg/mL. Plausible biosynthetic pathways corresponding to aldisine analogs of 1, 2, 4, and 5 were also discussed. Abstract :